THE RIGHT TO ENVIRONMENTAL PROTECTION IN SERBIA - BETWEEN ETHICS OF GOOD INTENTION AND ETHICS OF RESPONSIBILITY - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Summary: The paper focuses on formal and practical problems in the field of environmental protection, which occur as a consequence of omissions of the legislative and executive authorities in Serbia. The text analyzes the positive legislation and compliance of domestic legal regulations with international declarations and conventions ratified by our country (from the Stockholm Declaration and the Council of Europe Convention on Civil Liability for Damage Caused by Dangerous Activities to the Environment to the Rio Declaration), as well as with European Directives (EU Directive on Industrial Emissions) and Regulations (Regulation No. 525/2013 on monitoring and reporting of greenhouse gas emissions and reporting on other information relevant to climate change). The candidacy for equal membership in the European family of nations obliges the Serbian Parliament and the Government to make additional efforts in the direction of harmonizing our law with the European one. The paper takes a de lege ferenda approach, so the author explains the need to amend a number of laws, such as the Law on Environmental Impact Assessment, the Law on Strategic Environmental Assessment, the Law on Fees for the Use of Public Goods and the Law on Budget system, as well as the enactment of the Law on Climate Change and the Serbian Civil Code as soon as possible (in which dilemmas that hinder the subjects of law in using the environmental lawsuit as an instrument of environmental protection should be resolved). An unacceptable deviation from one of the fundamental principles established by the Rio Declaration was pointed out, which brings with it a number of structural problems and the inability of both the Green Fund institutions and a number of organizations that focus on ecology. The consequences of the discrepancy between the intentions proclaimed by the Constitution of Serbia and the National Strategy of Serbia for the accession of Serbia and Montenegro to the European Union from 2005 on the one hand and the absence of adequate legislative and executive activities in environmental protection, on the other hand, are obvious in the reports of the European Commission and the European Environment Office, as well as in the health risk and increased mortality of a large number of citizens of Serbia and other European countries, due to harmful emissions that cause pollution of air, water and soil in our country. In addition to the proposals for changes in the formal framework in the field of environmental protection, the paper points out the need to use those mechanisms of civil protection, such as environmental lawsuits (established by the Law on Obligations 1978), which is, by its nature, actio popularis and in that sense accessible to the widest range of subjects. The defense of the standards established by the Kyoto Protocol and the Basel Convention would, through the extensive use of this procedural instrument, be placed not only in the hands of representatives of the legislature and the executive, but also, the judiciary (conditionally, of course, because courts can decide only initiate a civil action, but not on its own initiative).
Keywords: environment; harmonization of legal regulations; environmental lawsuit